Career Guidance of Teenagers and their Sociocultural Development and Adaptation in Modern World of New Technologies - Zuyeva, Tatyana V.; Nyssanov, Adel T. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: Compilation and partial testing of a career guidance program for students with special training in high school. Background: A modern teenager is formed as a personality in the conditions of a constant increase of prestige of a profession and readiness of the labour market for the formation of subject-matter specialists. Each teenager chooses a profession based on their current market situation and their perception of it not only by technical capabilities but also by social, cultural, and value orientations. In this regard, early identification of professional preferences and the establishment of a system of work with schoolchildren, point-oriented to the choice of a profession, is relevant. The relevance of the work is determined by the fact that such a choice is made without the ability to determine success in a specific professional field in advance. Method: The main content of the formation of teenagers' knowledge and skills for professional activities in the sociocultural environment were the disciplines of the variable part of the curriculum and the special course "Features of professional activity in the sociocultural environment”. The methodology for creating and implementing a special course is focused on the formation of the basic components of readiness for professional activity in the sociocultural environment: personal, interactive, and reflective (evaluative). Results: The article not only analyses the current experience of career guidance but also proposes to analyse the situation of teenagers' susceptibility to such guidance basing on different components. The practical significance of the study is determined by long-term projects, which are considered as a probabilistic improvement of socio-economic development and improvement of the quality of work in various industries, and at the personal level – sociocultural development and socialisation of teenagers. Conclusion: The career guidance of teenagers should combine not only a story of a target audience about the benefits of a profession, but also about ways of communication and formation of a definition of technological way to bring information about the choice of profession.